Measuring nurses’ moral courage: an explorative study - Konings, Kasper Jean-Pierre (Nursing ethics, 2022)
Background:The 21-item Nurses’ Moral Courage Scale was developed and validated in 2018 in Finland with the purpose of measuring moral courage among nurses.Objectives:The objective of this study was to make a Dutch translation of the Nurses’ Moral Courage Scale to describe the level of nurses’ self-assessed moral courage and associated socio-demographic factors in Flanders, Belgium.Research design:A forward–backward translation method was applied to translate the English Nurses’ Moral Courage Scale to Dutch, and a pilot study was conducted to improve readability and understandability. A non-experimental, descriptive cross-sectional exploratory design was used to conduct a survey. Descriptive analysis was used.Participants:The data were collected from a convenience sample of 559 nurses from two hospitals in Flanders.Ethical considerations:Ethical approval was obtained from the university ethics committee, permission to conduct the study was obtained from the participating hospitals. Participants received a guide letter and gave their informed consent.Findings:The readability and understandability of the Dutch Nurses’ Moral Courage Scale were positively evaluated, and the scale revealed a good level of internal consistency for the total scale (α = .914) and all subscales. Nurses’ mean score of the 21-item Nurses’ Moral Courage Scale was 3.77 (standard deviation = 0.537). The total Nurses’ Moral Courage Scale score was associated with age (p < .001), experience (p < .001), professional function (p = .002), level of education (p = .002) and personal interest (p < .001).Discussion and Conclusion:The Nurses’ Moral Courage Scale was successfully translated to Dutch. The Flemish nurses perceived themselves as morally courageous, especially when they were in a direct interpersonal relationship with their patients. Acting courageously in ethical dilemmas that involved other actors or organizations appeared to be more challenging. The results strongly suggest the important role of education and ethical leadership in developing and supporting this essential virtue in nursing practice.